A Case of Markedly Elevated Isolated Alkaline Phosphatase in the Third Trimester of Pregnancy - Courtney T. Connolly; Olivia Grubman; Zainab Al-Ibraheemi; Tatyana Kushner (Case Reports in Obstetrics and Gynecology)
Background. Alkaline phosphatase (ALP) is an enzyme produced by the liver, small intestine, bone, and kidneys as well as the placenta during pregnancy. ALP levels may increase up to twice the normal limit during pregnancy secondary to placental release and fetal bone growth. Rare case reports of extremely elevated levels of ALP during pregnancy have demonstrated possible association with adverse pregnancy outcomes. Case. The patient is a 36-year-old G2P1001 who was found to have extremely elevated ALP levels during pregnancy after presenting with bilateral lower leg swelling and rash after receiving the Pfizer COVID-19 vaccine. She subsequently developed intrahepatic cholestasis of pregnancy and preeclampsia. ALP peaked at 2,601 U/L immediately prior to delivery at 36 weeks 1 day. She was followed postpartum, and her ALP levels had nearly normalized by 15 weeks postpartum. Conclusion. Our case demonstrates a rare report of an extremely elevated level of ALP in the setting of multiple adverse pregnancy outcomes, including preterm delivery, preeclampsia without severe features, and intrahepatic cholestasis of pregnancy.